A quality‐adjusted survival time without symptoms or toxicities analysis of glasdegib plus low‐dose cytarabine versus low‐dose cytarabine as initial therapy for acute myeloid leukemia in patients who are not considered candidates for intensive chemotherapy. Issue 19 (22nd July 2020) - Solem, Caitlyn T.; Bell, Timothy J.; Kwon, Youngmin; Cappelleri, Joseph C.; Johnson, Courtney; Bhattacharyya, Helen; Hoang, Caroline J.; Cortes, Jorge E.
Abstract : Background: In a randomized study, glasdegib (a hedgehog inhibitor) plus low‐dose cytarabine (LDAC) significantly prolonged survival in comparison with LDAC in patients with acute myeloid leukemia (AML). A quality‐adjusted time without symptoms of disease progression or toxicity (Q‐TWiST) approach was used to evaluate comparative quality‐adjusted survival. Methods: Overall survival was partitioned into the following: time with any treatment‐emergent grade 3 or higher adverse events (TOX); time without symptoms of disease progression or toxicity (TWiST); and time after treatment discontinuation due to insufficient clinical response, relapse, or death time after progression (REL). Q‐TWiST was calculated by multiplying the restricted mean time in each state by respective utilities and then summing up the utility‐adjusted time. Results: At 20 months of follow‐up, the survival probabilities for the glasdegib‐LDAC arm and the LDAC arm were 28.2% and 7.9%, respectively. Glasdegib‐LDAC patients (n = 78), in comparison with LDAC patients (n = 38), had significantly longer mean TWiST (+3.4 months; 95% confidence interval [CI], 1.8‐5.2 months) and TOX (+0.8 months; 95% CI, 0.1‐1.6 months) and longer but nonsignificant REL (+0.3 months; 95% CI, −1.9 to 2.3 months). Q‐TWiST was 4.0 months (95% CI, 2.1‐5.8 months) longer with glasdegib plus LDAC, and this translated into a 75% relative improvement in quality‐adjusted survival with respect to LDAC. Results were robust to the length of follow‐up (6‐24 months) and remained significant when all adverse events, regardless of grade, were included. Conclusions: These results suggest that most of the survival benefit from glasdegib plus LDAC versus LDAC alone is TWiST, and this represents added time in relatively "good" health. These results support the clinical value of glasdegib plus LDAC as initial therapy for AML in patients for whom intensive chemotherapy is not an option. Abstract : This analysis suggests that most of the survival benefit from glasdegib plus low‐dose cytarabine (LDAC) in comparison with LDAC alone is time without symptoms of disease progression or toxicity, which represents added time in relatively "good" health. These results support the clinical value of glasdegib plus LDAC as an initial therapy for acute myeloid leukemia in patients for whom intensive chemotherapy is not an option.